(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2007)
The silica and oxygen activities nave been investigated used E M F method in melts of quoternary systems SiO2 – Al2O3 – MgO – CaF2 at 1673 K.